THE ROLE OF MASS MEDIA IN REPORTIG NATURAL DISASTERSN: A MULTIMODAL CRITICAL DISCOURSE ANALYSIS OF GUNTHER-KRESS PHOTOJOURNALISM OF THE GREAT EASTERN JAPAN DISASTER IN THE YOMIURI SHINBUN DAILY 11-13 MARCH 2011 - Amanullah, Moh Gandhi; Faruk, Faruk; Irawanto, Budi (International Review of Humanities Studies, 2026)
This article examines the role of the Japanese newspaper Yomiuri Shinbun in covering the great East Japan disaster on March 11-13, 2011. This study uses a quantitative and qualitative approach, with content analysis methods and Gunther-Kress multimodal critical discourse analysis methods on 98 photos published by the newspaper. The results show that the newspaper published a special edition twice, with photos that did not show photos of the deceased victims, creating a distance between the reader and the subject. Most of the photos were taken from a distance, indicating a lack of interaction and showing that the victims did not need help. The theme highlights physical damage more than mitigation efforts or victims, with an imbalance in regional representation. Qualitative analysis shows that techniques such as aerial photography provide a broad picture of the impact of the disaster, but reduce emotional closeness. The flat facial expressions emphasize the resilience of the community. These findings confirm that the visuals in disaster coverage shape emotional narratives that influence public response, and the importance of coverage strategies in understanding and responding to disasters.